Runoff, sediment load and land use/cover change relationship: the case of Maybar sub-watershed, South Wollo, Ethiopia. Issue 1 (2nd January 2017) - Tesfaye, Gebremedhin; Assefa, Abera; Kidane, Desale
ABSTRACT: This study analysed the land-use dynamics and its effects on rainfall–runoff and runoff–sediment relationships at Maybar sub-watershed, Ethiopia. The study compared land use land cover change (LULCC), runoff and sediment load for 1980s, 1990s and 2000 years. A base map produced from ground base survey, aerial photograph, spot images and field visit/interview had been carried out for land cover analysis. Double mass curve with trend curve was used to evaluate the effect of LULCC on rainfall–runoff and runoff–sediment yield relationships. The results showed that during 1990s forest land increased while agricultural and grassland decreased, whereas during 2000s agricultural land increased and forest land decreased. Consequently, the annual slope of trend curve (STC) of rainfall–runoff and runoff– sediment load during 1980s was more pronounced compared with 1990s. Similarly, the annual STCs of 2000s were higher than 1990s despite it is not statistically significant. This implies that, the accumulative annual runoff and sediment load increases more rapidly from 1982 to 1989 than that from 1992 to 1999, and from 2000 to 2006. Hence, the runoff and sediment load obtained during 1980s was higher than 1990s and 2000s was more than 1990s with similar rainfall/runoff. These can be explained by the historic land-use dynamics. Therefore, in order to reduce soil loss, flood occurrence and sediment load, all concerned stakeholders such as local governments, planners and farmers should pay attention to apply appropriate land use and watershed management practices in the studied watershed.